Analisis Perencanaan Lingkungan Internal untuk Meningkatkan Mutu Kelembagaan di MA MILBoS - Solihin, Agung (Perkumpulan Peneliti dan Pegiat Literasi, 2026)
Research on Islamic school quality management has predominantly focused on external environmental factors, while the systematic relationship between religious organizational culture, digital readiness, and institutional quality in Indonesian madrasahs remains underexplored. This study aims to analyze internal environmental planning for improving institutional quality at MA Milbos Bogor City. The research questions are: what is the current condition of the madrasah's internal environment, what are the supporting and inhibiting factors for quality improvement, and what internal planning strategies can be formulated? This study employed a qualitative case study approach. Data were collected over three months through semi-structured interviews, participatory observation, and documentation with eight key informants are the Principal, five teachers, and two administrative staff, selected purposively. Data analysis followed the Miles, Huberman, and Saldana model. The findings indicate that MA Milbos is at a developing stage. Its key strengths are harmonious religious work culture and educator commitment, while constraints include uneven teacher discipline, limited technology-based learning facilities, and manual administrative processes. Five internal planning strategies were formulated. This study contributes to the contextualization of Total Quality Management theory for madrasah governance by integrating religious-cultural dimensions and digital readiness indicators